Effect of solution treatment on magnesium sacrificial anode - Norliawati Nor Azman (Universiti Malaysia Perlis, 2008)
The main objective of this study is to determine the effect of solution treatment period on the corrosion behavior of magnesium anode. Commercial high potential magnesium anode was heat-treated at 3000C for 3, 6 and 9 hours in high temperature oven. After quenched, all samples were aged at 1500C for 8 hours. Electrochemical testing such as open circuit potential, Tafel plot, potentiodynamic anodic polarization were carried out by Gambry potentiostat/ galvanostat equipment. It was found that as-received high potential magnesium anode exhibit high corrosion potential (-1680 mV vs SCE) and also high corrosion rate (4.148 x 103 mm/year). It was also found that by the increasing the solution treatment period, the corrosion rate was reduced. The appearance of needle like structure was found increases the corrosion rate of magnesium anode.